Evaluation of activity kinetics in breast milk and calculation of the resulting effective radiation dose after 99mTc-MIBI scintigraphy of a breastfeeding women - Happel, Christian; Gröner, Daniel; Kranert, Wolfgang Tilman; Grünwald, Frank (Nuklearmedizin - NuclearMedicine, 2022)
Introduction In breastfeeding women, the indication for scintigraphic imaging is strongly restricted due to potential transition of the radiopharmaceutical to the child via breast milk. The potential activity uptake of the breastfed child depends on the chemical compound of the radio pharmaceutical as well as biokinetics and metabolism in the maternal body.Methods In the presented case 99mTc-MIBI scintigraphy was performed in a breastfeeding woman with sonographically suspicious thyroid nodules. Breastfeeding was interrupted for 30 hours and the breast milk during this period was collected and analysed to determine the excreted activity and the potentially resulting dose to the breastfed child.Results Activity concentration in the first breast milk sample (1.83 hours after administration of 500 MBq 99mTc-MIBI) was 380 Bq/mL, resulting in an absolute activity of 50 kBq for a sample size of 132 mL. Subsequently activity concentration decreased to 6 Bq/mL (29.8 hours p.i.). The calculated effective half-life of the secretion of 99mTc-MIBI via breast milk was 4.7 hours. The potentially resulting effective dose for the breastfed child was 13.4 µSv (ICRP80: dose coefficient: 0.13 mSv/MBq for 99mTc).Conclusion Time activity curve showed a rapid decrease of the 99mTc-MIBI activity secreted to the breast milk. More than 90 % of the total secreted activity is attributable to the first 12 hours after administration. Therefore, an interruption of breastfeeding of 24 hours seems to be adequate.
Keywords: Breast milk; 99mTc-MIBI scintigraphy; radiation dose